A Comprehensive Review Of E-Banking: Unravelling Trends, Challenges, And Future Directions - Sweta Savaliya; Dr. Vishal Khasgivala (Educational Administration: Theory and Practice, 2024)
In the ever-evolving landscape of financial services, electronic banking, or E-banking, stands as a pivotal domain that has garnered significant attention from researchers, practitioners, and policymakers alike. As we navigate the digital age, where technological advancements redefine the contours of conventional banking, a comprehensive review of the existing literature on e-banking becomes imperative. This paper aims to synthesize the wealth of knowledge accumulated in this domain, providing a nuanced understanding of the trends, challenges, and future directions that have emerged through extensive research and practical implementations. This review paper will navigate through the key themes that have emerged in the extensive body of literature on e-banking. This paper embarks on a journey to dissect the e-banking services offered by both public and private sector banks in India, unravelling the distinct approaches, challenges, and triumphs that characterize their foray into the digital domain